Modernism and the new Spain Britain, cosmopolitan Europe, and literary history - Rogers, Gayle, 1978- (Oxford : Oxford University Press, 2012)
Drawing on transnational literary studies, periodical studies translation studies, and comparative literary history 'Modernism and the New Spain' illuminates why Spain has remained a problematic space on the scholarly map of international modernisms.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Modernism (Literature) -- Spain; Spain -- In literature; Spain -- Intellectual life -- 20th century; Spanish literature -- 20th century -- History and criticism; Spanish literature -- English influences; English literature -- 20th century -- History and criticism; English literature -- Spanish influences